Comparison of live donor predonation and post‐transplant kidney volumes and glomerular size in pediatric patients weighing less than 15 kg – a retrospective study. (23rd March 2020) - Muramatsu, Masaki; Hamasaki, Yuko; Mizutani, Toshihide; Takahashi, Yusuke; Hashimoto, Junya; Kubota, Mai; Oguchi, Hideyo; Yonekura, Takashi; Sakurabayashi, Kei; Aoki, Yujiro; Shinoda, Kazunobu; Itabashi, Yoshihiro; et al.
Abstract: Renal transplantation of adult‐size kidneys presents a size mismatch in small children. This study presents a comparison of live donor predonation and recipient post‐transplant kidney volumes (k‐vol) and glomerular size at 1 year after transplantation. We analyzed 47 pediatric renal transplant recipients weighing <15 kg between 2009 and 2017. The k‐vol before and 1 year after transplantation and glomerular size at implant and 1 year post‐transplant were evaluated. We estimated the relationships between these changes and graft function, and the factors associated with k‐vol. Pretransplant k‐vol was 158.1 ± 25.1 ml, and the k‐vol at 1 year post‐transplant was significantly reduced by −17.2% to 132.3 ± 27.3 ml ( P  < 0.001). Implant glomerular size showed the diameter was 165.3 ± 15.1 µm and the area 20 737.1 ± 3230.6 µm 2 . One‐year post‐transplant, the glomerular diameter was 150.6 ± 11.4 µm and the area 17 428.3 ± 2577.9 µm 2, significantly reduced compared with implantation values (both P  < 0.001). The change in k‐vol was affected by pretransplant abdominal cavity (ml/200 ml cavity volume, partial regression coefficient = 0.029, SE = 0.009, P  = 0.004) and recipient's weight gain (ml/5% of weight gain, partial regression coefficient = 0.020, SE = 0.006, P  = 0.002). In small pediatric transplants, an adult‐size kidney is acceptable with reduction in k‐vol. Moreover, the post‐transplant k‐vol might be regulated by pretransplant physique and post‐transplant somatic growth.